Coating by the Cold Spray Process: a state of the art - Mario Guagliano; Ramin Ghelichi (Fracture and Structural Integrity)
A brief description of cold spray coating process is presented. This paper intends to review some the previous works which are mostly about the influences of the cold spray parameters, mostly the surface ofthe substrate, on the deposition efficiency (DE). Almost all the important parameters, with more focus on the roughness of the substrate, on increasing the DE are briefly studied; this review also includes a description of application of cold spray and of some important effect of this method on substrate properties.On this basis, some possible development in this field of research are drawn and discussed.